Pengaruh Frekuensi Pengendalian Gulma Secara Manual Terhadap Pertumbuhan dan Produksi Padi Sawah (Oryza Sativa L.) Dengan Metode Sri - Winarto, Febby Khoila; Zuhry, Elza; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research was to find the effect of frequency by manually weeds control for growth and the production of paddy field (Oryza sativa L.) by SRI methode. This research was conducted in Balai Benih Induk Hortikultura at Kaharuddin Nasution street, Padang Marpoyan, Pekanbaru. This research held for 5 months, started in November 2011 until March 2012. This research use Randomized Block Design (RBD) that consists of 4 treatments and 3 replications. These treatments consist of once weeding ( 30 days after planted), twice weeding ( 20, 40 days after planted), third weeding (20, 30, 40 days after planted) and fourth weeding ( 10, 20, 30, 40 days after planted) manually. Parameters measured were plant height (cm), number of maximum nhymps (stem), the outgoing panicles (days), the number of productive tillers (seed), dried milled rice production per clump (g), 1000 seed weight (g). Data was analyzed by analysis of variance and further test by Duncan Multiple Range Test (DNMRT) at the level of 5%. The research showed that the treatment of frequency by manually weed control were not significant to all parameters (parameters measured were plant high, number of maximum nhymps, the outgoing panicles, the number of productive tillers, 1000 seed weight ) except in parameter of dried milled rice production per clump and the manually weeding of once frequency (30 days after planted) has yield 15,2 t/ha. Keyword: Paddy field, SRI, weed control